2006
DOI: 10.1029/2006rs003475
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Schumann resonance parameters in horizontal magnetic and electric fields according to observations on the Kola Peninsula

Abstract: [1] The measurements of horizontal electric components at extremely low frequencies (0.1-20 Hz) have been started in the high-latitude observatory of Lovozero in the Kola Peninsula. It is found that the electric components are not less informative than the horizontal magnetic ones for Schumann resonance study. The diurnal variations in amplitude, frequency, and bandwidth of the first Schumann resonance mode in the electric W-E and N-S components are similar to the variations in the magnetic H and D components,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The relation between B NS -E EW and B EW -E NS can be observed by looking at the spectra of the electric fields averaged in Figure 5. The presence of a horizontal component in the electric field implies a vertical component of the Poynting vector [Roldugin et al, 2006]. Another interesting behavior because of the orientation of the magnetometers can be observed.…”
Section: Toledo-redondo Et Al: Schumann Resonances From Mt Records Dmentioning
confidence: 79%
See 1 more Smart Citation
“…The relation between B NS -E EW and B EW -E NS can be observed by looking at the spectra of the electric fields averaged in Figure 5. The presence of a horizontal component in the electric field implies a vertical component of the Poynting vector [Roldugin et al, 2006]. Another interesting behavior because of the orientation of the magnetometers can be observed.…”
Section: Toledo-redondo Et Al: Schumann Resonances From Mt Records Dmentioning
confidence: 79%
“…The first has its central value at around 7.8 Hz, the second mode moves around 14 Hz, and the third mode does so at around 20.5 Hz. It is interesting to see the correlation of the central frequency between the NS magnetic component and the EW electric component and vice versa [Roldugin et al, 2006]. In many campaigns, a shift is observed between B NS and B EW and, consequently, the same occurs with the electric components.…”
Section: Interseasonal Studymentioning
confidence: 99%
“…In this work, a comparison of SR values obtained using both types of fitting functions has been carried out. The linear terms are proposed in Roldugin et al () to describe the decreasing with frequency noise from input electronic circuits, with B < 0. Another possible origin for the linear terms is that, despite higher order modes are not present in the calibrated region, the effect of their low‐frequency tails cannot be disregarded.…”
Section: The Procedures Used In the Elf Station At Sierra Nevadamentioning
confidence: 99%
“…El Niño phenomenon is also studied in terms of its relationship with variations in SR frequencies (Sátori, ; Sátori & Zieger, ). SR studies based on long‐term measurements taken by different stations can be found in Kulak et al (), Ondrášková and Ševćík (, ), Ouyang et al (), Roldugin et al (, ), and Zhou et al ().…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the long‐period variations are not represented. Additionally, the available observational components are limited to the magnetic field data, in practice, since the Earth’s surface is not an ideal conductor (Gregori & Lanzerotti, 1979; Roldugin et al., 2006), clear SRs can still be recorded in the horizontal electric field, which can help us to more comprehensively analyze the SR phenomenon. In this paper, we analyze the quasi‐continuous data from 10 electromagnetic stations over the last 9 years to obtain the common aspects concerning SR seasonal and interannual variations and compare these signatures among each other and with the results reported by other authors.…”
Section: Introductionmentioning
confidence: 99%